Avaliação das atividades leishmanicida, tripanocida e imunomoduladora de extratos de raízes de Lonchocarpus cultratus - Staffen, Izabela Virginia (2020)
Chagas disease and Leishmaniasis are neglected pathologies that presents a limited availability of medicines. Several sources, mainly plants, compose the search for new drugs capable of combating the protozoa involved in those diseases. This work aimed at evaluating the anti-Trypanocidal and anti-Leishmania action of Lonchocarpus cultratus root extracts; establish its cytotoxicity and relationship with the immune system. Hexanic, methanolic, and dichloromethane (DCM) extracts of the L. cultratus root were used on mice peritoneal macrophages of C57BL/6 and BALB/c mice and on RAW 264.7 macrophages, T. cruzi tripomastigote and amastigote forms as well as promastigote and amastigote forms of Leishmania amazonensis (L. amazonensis). Macrophages and both forms of the parasites were treated with different concentrations (1 to 175 µg/mL) of the extracts diluted in RPMI medium. With different intensities, all presented significant leishmanicidal and trypanocidal activity. Hexanic and methanolic extracts did not affect cell viability at the tested concentrations, and DCM was toxic at concentrations above 15 µg/mL. The extracts did not estimulate the secretion of Nitric oxide (NO), however, hexanic showed a strong inhibition power of liberating NO for peritoneal macrophages stimulated with LPS in all tested concentrations. Methanolic presented moderate inhibitory activity at concentrations until 15 µg/mL. There was no detection of significative levels of cytokine IL-1β and IL-10 in the supernatant of infected macrophages with L. amazonensis amastigotes post-treatment with the extracts. Future in vitro studies are required to confirm those results.